2008
DOI: 10.1002/app.28379
|View full text |Cite
|
Sign up to set email alerts
|

Novel thermally and mechanically stable hydrogel for enzyme immobilization of penicillin G acylase via covalent technique

Abstract: j-Carrageenan hydrogel crosslinked with protonated polyethyleneimine (PEI 1 ) and glutaraldehyde (GA) was prepared and evaluated as a novel biocatalytic support for covalent immobilization of penicillin G acylase (PGA). The method of modification of the carrageenan biopolymer is clearly illustrated using a schematic diagram and was verified by FTIR, elemental analysis, DSC, and INS-TRON using the compression mode. Results showed that the gels' mechanical strength was greatly enhanced from 3.9 kg/cm 2 to 16.8 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 28 publications
3
57
0
Order By: Relevance
“…However, expensive enzymes are not favored to be used in industries in the Free State as they are difficult to be separated from the products (Figure 1(a)) and consequently are lost after the first use. They were alternatively immobilized on solid supports (Figure 1(b)) so that they can be easily separated from the products by simple filtration or using a fluidized magnetized bed reactor system [7][8][9][10][11][12][13][14].…”
Section: Methods Of Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, expensive enzymes are not favored to be used in industries in the Free State as they are difficult to be separated from the products (Figure 1(a)) and consequently are lost after the first use. They were alternatively immobilized on solid supports (Figure 1(b)) so that they can be easily separated from the products by simple filtration or using a fluidized magnetized bed reactor system [7][8][9][10][11][12][13][14].…”
Section: Methods Of Immobilizationmentioning
confidence: 99%
“…The most widely studied system is the production of penicillin G using immobilized cells of Penicillium chrysogenum [4]. In a recent study by Elnashar et al, they were successful to covalently immobilize pencillin G acylase on carrageenan modified gels with retention of 100% activity after 20 reuses [9]. procedures In addition to the above applications, we will focus the light on some important applications as solving the problem of lactose Intolerant people, production of fructose for diabetics and for people on diet regimen, and treatment of rheumatoid arthritis and joint diseases.…”
Section: Antibiotics Productionmentioning
confidence: 99%
“…They were alternatively immobilized on solid supports (Fig. 1b) so that they can be easily separated from the products by simple filtration or using a fluidized magnetized bed reactor system (Danial et al, 2010, Elnashar, 2010aElnashar et al, 2008Elnashar et al, , 2009aElnashar et al, , 2009bYassin 2009a, 2009b;Mansour et al, 2007).…”
Section: Methods Of Immobilizationmentioning
confidence: 99%
“…The most widely studied system is the production of penicillin G using immobilized cells of Penicillium chrysogenum (Ogaki et al, 1983). In a recent study by Elnashar et al, they were successful to covalently immobilize pencillin G acylase on carrageenan modified gels with retention of 100% activity after 20 reuses (Elnashar et al, 2008). Penicillin Variant H -6-Amino-penicillanic acid (6-APA)…”
Section: Antibiotics Productionmentioning
confidence: 99%
“…This is probably because some of the negatively charged sulfate ester reacted with the positively charged amine groups on PEI and this resulted in physicochemical changes of carrageenan. Indeed, a previous study [16] showed that protonated amine groups of PEI interact with sulfate groups of κ-carrageenan (κC), enabling the formation of the PEI-κC polyelectrolyte complex.…”
Section: Characterizationmentioning
confidence: 99%